PERSONNEL ISSUE IN CUSTOMS ACTIVITIES IN TURKESTAN (1917-1924) (Scientific journal of the Fergana State University, 2024)
This article examines the history of customs work in the Turkestan Autonomous Soviet Socialist Republic, especially the issue of personnel working in customs offices and checkpoints of the country. Also included in scientific circulation was the process of creating a mechanism for accounting, training and distribution of personnel in the customs system, forming a nomenclature and personnel apparatus, as well as the results obtained by analyzing the studied archival documents and scientific literature data.